A Unique European Governance Structure – Office of the High Representative in Bosnia and Herzegovina Basis of Its Legitimacy and Controversial Accountability - Gutic-Bjelica, Biljana (Észak-magyarországi Stratégiai Füzetek, 2024)
In order to assess the successes and failures of Bosnia and Herzegovina’s (BiH) challenging road towards a fully functional democratic state aiming at membership in the European Union (EU), this paper examines the state-building process in BiH, and the transition from the post-Dayton political development, the work of the interim, ad-hoc political institution of the Office of the High Representative (OHR) in BiH, as well as the justification – if any - of its future existence and operation. Guided by the coordination dilemma, the research question of this paper is a reflection on the challenges of self-enforcing democratic institutions and how the OHR substitutes for it. This paper claims that the original purpose of the Dayton Peace Agreement (DPA) was to create a powerful yet limited institution of the OHR, one that is to be given sufficient power to institute behaviour, but is prevented from abusing its power. However, this purpose deviated in the years that followed the signing of the DPA, creating and institution which doings resemble liberal imperialism. The hypothesis of the paper is that the OHR has been abusing its power and that it is time to close it because it is no more a substitute for the self-enforcing democratic institutions. This paper claims that the problem of political officials’ lack of respect for the political and economic rights of citizens they administer, as investigated by Weingast, is one of the central features of the operation of the OHR in BiH. The novelty of the paper lies in the attempt to test if OHR could be a case that could serve as a very good field to test Weingast’s model (1997).